2018
DOI: 10.1002/jbm4.10062
|View full text |Cite
|
Sign up to set email alerts
|

Variables Reflecting the Mineralization of Bone Tissue From Fracturing Versus Nonfracturing Postmenopausal Nonosteoporotic Women

Abstract: Women with equivalent areal bone mineral densities may show a different fracture incidence due to differences in bone intrinsic quality. Previously, Fourier transform infrared spectroscopic imaging (FTIRI) on the same iliac bone biopsies reported here, showed that the only significantly different variable was the carbonate/phosphate ratio, which was decreased in the fracturing group. Nanoindentation showed that fracturing bone was less mechanically heterogeneous than nonfracturing bone and could propagate dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Half of all fragility fractures occur in individuals with osteopenia (BMD T-score < −1.0, but >−2.5), rather than osteoporosis (T-score < −2.5) ( Kanis et al, 1994 ; Fonseca et al, 2014 ). As with GC and diabetic patients, studies of bone blood flow in BMD-matched osteopenic patients who have (or have not) experienced fragility fractures, could be used to examine the relationship of bone blood flow to excessive bone fragility ( Rizzo et al, 2018 ; Polly et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Half of all fragility fractures occur in individuals with osteopenia (BMD T-score < −1.0, but >−2.5), rather than osteoporosis (T-score < −2.5) ( Kanis et al, 1994 ; Fonseca et al, 2014 ). As with GC and diabetic patients, studies of bone blood flow in BMD-matched osteopenic patients who have (or have not) experienced fragility fractures, could be used to examine the relationship of bone blood flow to excessive bone fragility ( Rizzo et al, 2018 ; Polly et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, many crucial biological processes were strongly associated with miRNAs, such as cell differentiation, apoptosis, as well as proliferation [ 15 ]. Some research showed that certain miRNAs can be involved in bone metabolism, bone turnover as well as bone development, so as to regulate the occurrence and progress of OP [ 16 ]. A study have shown that miR-133 expression is increased during estrogen deficiency, regulating osteogenic differentiation of mesenchymal stem cells, and causing postmenopausal OP [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…OP is one of the common complications of patients with type 2 diabetes mellitus (T2DM), causing great morbidity and seriously affecting the quality of life of patients ( 2-4 ). Currently, the main therapeutic methods for elderly patients with T2DM and OP include calcium and vitamin D supplements, physical exercise, specified diet and high quality nursing, yet the occurrence and progression of OP in elderly patients with T2DM cannot be effectively controlled ( 5 , 6 ). Therefore, it is of great clinical significance to explore new therapeutic methods and drugs for patients with T2DM and OP.…”
Section: Introductionmentioning
confidence: 99%